2008
DOI: 10.1375/acri.41.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Girls Troubles, Girls' Delinquency, and Gender Responsive Programming: A Review

Abstract: T his article begins with a consideration of the interconnected troubles and needs that research has documented for girls who become enmeshed in the juvenile justice system. Special attention is given to findings from research that gives girls in the system some 'voice' in explaining what services and programs they need and want. After offering some explanation of the gap in programs and services for girls, the article notes the failure of evaluation results to shed light on effective program models, and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 30 publications
9
103
0
1
Order By: Relevance
“…However, studies also show that delinquents often do not receive the care they need in residential and community settings [55]. One possibility, beyond the scope of our study, is that young women may be particularly underserved if treatment centers lack beds or program slots for girls and young women, a phenomenon evident in juvenile detention, which has historically been tailored to serve males [56]. In these settings, gender differences may be overlooked delinquent girls may have few intervention programs available [57].…”
Section: Implications For Policy Programming and Practicementioning
confidence: 94%
“…However, studies also show that delinquents often do not receive the care they need in residential and community settings [55]. One possibility, beyond the scope of our study, is that young women may be particularly underserved if treatment centers lack beds or program slots for girls and young women, a phenomenon evident in juvenile detention, which has historically been tailored to serve males [56]. In these settings, gender differences may be overlooked delinquent girls may have few intervention programs available [57].…”
Section: Implications For Policy Programming and Practicementioning
confidence: 94%
“…Due to behavior issues that are commonly associated with teenage mothers, "conclusions can be drawn regarding the risk factors associated with teenage pregnancy, the link between teenage pregnancy and delinquency, and the characteristics of those most likely to become teenage parents" (Buffkin & Luttrell, 2010). Chesney-Lind et al (2008) found that many of the teen mothers in the detention centers felt that they did not receive the essential tools that are needed to be better parents and productive citizens upon being released.…”
Section: ) Overrepresentationmentioning
confidence: 99%
“…Prior to enactment of the 1996 legislation, the majority of young mothers who went on welfare stayed on the rolls for at least two years with many reaming much longer" (Miranne & Young, 2002). Not only does teenage mothers presence affect legislation and welfare reform, but on the front end the lack of education leads to continuous welfare recipients, this is where the board of education becomes an affected agency because of truancy from absenteeism and truancy trickles down into the juvenile justice system, where there is a lack of case studies and support groups that offer the essential tools for growth into productivity as adults (Liefeld & Solomon, 1998;Miranne & Young, 2000;Chesney-Lind et al, 2008).…”
Section: Prior Researchmentioning
confidence: 99%
See 2 more Smart Citations